The Existence of Marriage Post the Constitutional Court Decision: As a Right or a Prerequisite? - Nurul Hikmah; Syahid Akhmad Faisol; Mohd Aderi Che Noh (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
The practice of marriage is always closely related to the arrangements in religious law and state law. This research aims to answer two legal issues, namely the existence of marriage after the Constitutional Court Decision No. 24/PUU-XX/2022 and the implications of the Constitutional Court Decision No. 24/PUU-XX/2022 in the aspects of Islamic law and national law. This research is a normative legal research with case, conceptual, and legislative approaches. The findings of this research confirm that the existence of marriage after the Constitutional Court Decision No. 24/PUU-XX/2022 is not only seen as a human right as a freedom for everyone to enter into marriage. But it must be based on the values of religious law as a representation of the legality of marriage by the state. The orientation of the Constitutional Court Decision is important because KHI and the Marriage Law have the same perspective in viewing marriage as a prerequisite and not as a right. The practical contribution of this research is related to ideal legal policy, namely the need for affirmation and formulation in Indonesian legislation that marriages that do not aim to form families and are oriented towards continuing offspring are invalid in accordance with the aspects of maslahat mursalah and the Indonesian legal system.